@Home collective(ly): Opening doors and doing books with literacy-cast. (March 2023) - Wessel‐Powell, Christy; Buchholz, Beth A; DeHart, Jason; Frye, Elizabeth M; Ward, Devery; Vander Zanden, Sarah; Campbell, Elizabeth
Although isolating, lockdown also created unexpected opportunities for connection and inspiration. This article describes the lockdown literacies of a sibling pair, Marco and Mara, as they wrote digital texts/books for Literacy-Cast, a virtual, interactive literacy space offered by Appalachian State University from March 2020-present. Since lockdown began, this virtual space has been enacted 4-5 days weekly with 70-250 participants logging in from "home" to co-construct a multigenerational, multilingual, geographically-dispersed community engaged in reading, writing/composing, making, speaking, and listening. Literacy-Cast was imagined, built, and enacted collaboratively among faculty, laboratory school teachers, graduate-level teacher candidates, and children (and families) in grades K-5. We hear a lot about the limitations of virtual classrooms/learning (e.g., COVID "learning loss, " lack of engagement, unequal access), particularly in relation to historically marginalized communities, but rarely are we offered counter-narratives: examples where young children who live and go to school in these communities shaped the creation of new virtual spaces/places by making visible meaningful "at home" literacy/language practices, cultural artifacts, and people. Through invitations embedded in the multimodal texts/books shared on Literacy-Cast's digital bookshelf, children brought the community into their homes–bedrooms, kitchens, backyards, back porches, and backseats, reframing "home visits'' as sites/events for new kinds of community knowledge production. Research about home visits, educators visiting students' homes to learn about children's lives, has documented the impact of home environment awareness on school interactions, improved relationships between caregivers and teachers, typically focused on intervention supporting school-based achievement and school practices, often with unidirectional flow from school-to-home; however we conceptualize Literacy-Cast's daily activity as multidirectional "home visits, " where invitations to come over and play, read, and write together brokered relationships and strengthened a gamut of literacy practices for all participants. Through collaborative ethnography, we explore ways "home" (e.g., objects/people/practices/languages/events) became tools/co-authors for children's digital composing/making and, ultimately, home/community-making.